INTERPORTO QUADRANTE EUROPE VERONA - Stopka, Ondrej; Sulgan, Marian (Doprava a spoje, 2012)
At the beginning, the paper deals with the general facts of Interporto Quadrante Europe Verona Freight Village. There are also mentioned provided logistics, transport and others services in this object. They can be divided into nine groups. At the end of the article, the detailed characterisation of combined transport terminal ("Compact Terminal") located in this Freight Village is outlined.